Besaran Masalah Low Vision dan Kebutaan di Indonesia Serta Berbagai Faktor Risiko Riset Kesehatan Dasar 2007 Berskala Nasional - Yekti, Rabea P.; Tana, Lusianawaty (Pusat BTDK, 2009)
Objectives: To assess the magnitude of low vision and blindness problems in Indonesia generally, and specifically, to get low vision and blindness proportions, tracing the trend of problems magnitude, and inventarizing the suspected causes of those visual impairments. Methods: This study analyzed the secondary data collected in the national scope Basic Health Research (BHR) 2007. Enumerators peiformed questionnaires based interview for demographic characteristics, cataract, glaucoma, diabetes mellitus (DM), and hypertension histories, and also measured visual acuity without refractive error correction and calculated the body mass index. Pterygium, lens opacity, corneal scar, and strabismus were identified by enumerators using penlight assistance. Results: We analyzed 765,650 respondents data (6 years old and above). The low vision proportion among those people is 4.8% and the blindness proportion is 0.9%. Those severe visual impairment proportions are higher on females (low vision 5.4%:4,1%; blindness 1.3%:0.9%). All tested independent variables increase the visual impairment risks. Age is the most potential factor increasing the risk to get a visual impairment, followed by the lens opacity. Cataract history and lens opacity are the leading causes of visual impairments among people (30 years old and above). Conclusions: The low vision and blindness proportions due to correctable causes are still high in Indonesia. Those severe visual impairments maybe influenced by multi-factors. Further investigation to identify the definitive causes for severe visual impairment should be peiformed, especially in provinces with higher severe visual impairment proportion compared to the national proportion. Â Key words: Blindness, Low Vision, Basic Health Research, Cataract, Refractive Error.